Discovering the voice of women through Archetypes in Baba Bullay Shah’s verses - Alvina Wasim (Linguistics and Literature Review, 2019)
Baba Bullay Shah known as “the Rumi of Punjabi Sufi poetry” is a strong voice of defiance against the caste and class system of his times. He used the voice of women to denote his divine love in the traditions of Ibne Arabi but he strongly condemns the patriarchal repressive traditions through his poetry. He raises his objection through the archetypical characters against the mal-treatment of the women. The women have the quality of the divine love and devotion towards their loved ones but the society does not acknowledge their elevated status. This research tries to find out the ways through which he determines the roles of women in his poetry, using the archetypes from the local folk lore for his mystical love. This will also discover how Baba Bullay Shah objects to the treatment of women in its class and caste system divisions. This discovery is done through Berry’s (2009) matrix of deconstruction in the post structuralist manner, while using the model of “Tauheed” and categories of “Tareeqat”, from Ibne Arrabi’s Cosmology Model, for to reach the divine love.